Designing the Absence System of the Langkat DPRD Using the Website-Based Waterfall Method - Irhami, Zahara Reva; Fachri, Barany; Novelan, Muhammad Syahputra (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2024)
Currently, computer-based technology is needed in the development of business and industry to speed up and simplify work, especially fast and accurate information. In addition, the information processing process is also important to make the information more useful. The phenomenon that exists in this era of globalization is that there are still many people who are less effective in using computer-based information technology, one of which is the Langkat DPRD. The attendance mechanism in DPRD Langkat that is applied now can be said to be less efficient and effective, where everything is still done manually starting from data collection and calculation of attendance hours, outgoing hours, up to absent information, this has an impact on the time that is long enough in the process of calculating the recapitulation of attendance from DPRD Langkat members, as well as the form of attendance reports designed in the form of hardcopy which can lead to errors in data recording, making it difficult to search for data and can be feared to lose attendance data. The attendance system for members of the Langkat DPRD is an information system designed to process attendance data for members of the Langkat DPRD, namely meeting data, DPRD member data, and attendance data. This system was built using the waterfall method with the PHP programming language and using the Mysql database. The results of this system are expected to help the relevant institutions in managing the attendance of members of DPRD Langkat, so that computerized data will be stored in a centralized database and the performance of the attendance data collection system of DPRD Langkat members will be more effective and efficient.